Farm Mechanization and Farmers’ Preferences: Evidence from North Bank Plain Zone of Assam - Manjil Baruah,; Barman, Sundar; Afsana Rahman, (Indian Journal of Extension Education, 2025)
The study was conducted during 2022 in North Bank Plain Zone of Assam for assessing degree of farm mechanization, preferences toward farm machineries and farm operations as well as factors influences on extent of farm mechanization. Descriptive research design was followed for the study. A purposive cum stratified random sampling technique was used for selection of 120 farmers as respondents for study. Degree of farm mechanization was recorded from medium to high for majority of farmers with average farm mechanization area 27.52%.  Majority farmers showed medium level of preference towards farm mechanization but knapsack or power sprayer, portable milling machines, tractor mounted thresher, tractor with rotavators or cultivator were most preferred farm machineries. Irrigation, milling, plant protection, threshing and land preparation were the most preferred farm operation for mechanization. Six socio economic factors viz. farm size, innovativeness, extension contact, credit availability, training exposures and preferences for mechanization were positively and significantly contributed around 46% variation of farm mechanization. Governments and non-government organizations should put efforts for promoting farm mechanization by establishment of custom hiring center of preferred farm machineries, easy accessible of government assistance and strategic mobilization of resource poor farmers.